A Unique Lymphaticovenous Supermicrosurgery Training Curriculum: Reflections on Validation and Competency Thresholds. Issue 6 (June 2017) - Pafitanis, Georgios; Narushima, Mitsunaga; Harima, Mitsunobu; Ghanem, Ali; Myers, Simon; Koshima, Isao
Abstract : Summary: Supermicrosurgery is becoming a commonly used technique in various subspecialties of reconstructive surgery. However, there is a lack of standardization and validation in novel supermicrosurgical training. Current simulation training programs are not adequately focused on the challenges encountered during clinical supermicrosurgery practice. This article describes the authors' experience utilizing a supermicrosurgery competency-based training curriculum, in a simulation-based environment, toward safe clinical practice for lymphatic submillimeter supermicrovascular surgery. This article demonstrates the senior authors' (I.K.) Halstedian competency-based curriculum for lymphaticovenous anastomosis training. Further, a step-by-step training utilizing the chicken thigh and the living rat high fidelity simulation models, which subsequently allows supervised one-to-one clinical training with verified clinical competency outcomes, are demonstrated.